Combustion of Coconut coir for Bioproduction of Silica/Zeolite Nanoparticle for Dye Removal - Mahad Mohamed (School of Bioprocess Engineering, University Malaysia Perlis, 2019)
To synthesize the silica/zeolite nanoparticle using Coconut coir. To characterize the obtained silica/zeolite nanoparticles. To evaluate the potential utilization of silica/zeolite nanoparticle for the dye removal.